Effect of solution treatment on microstructure and mechanical properties of cast Al–3Li–1.5Cu–0.2Zr alloy. Issue 8 (28th April 2016) - Peng, Yu; Chen, Antao; Zhang, Liang; Liu, Wencai; Wu, Guohua
Abstract: Abstract : The effect of solution treatment (ST) on the microstructure and mechanical properties of cast Al–3Li–1.5Cu–0.2Zr alloy was investigated. Results showed that the volume fraction of secondary phases (Al2 Cu, Al3 Li) decreased obviously after ST. It was found that the strengthening of Al–3Li–1.5Cu–0.2Zr alloy was a balance of the precipitation strengthening, residual phase strengthening and fine grain strengthening. The residual phase strengthening and fine grain strengthening decreased with increasing the solution temperature and time, while precipitation strengthening increased. After ST at 560 °C for 40 h, the elongation of Al–3Li–1.5Cu–0.2Zr alloy reaches the highest value of 22.1%. In addition, the tensile properties are up to the highest values, ultimate tensile strength of 359 MPa and elongation of 3.5% after optimal ST at 560 °C for 40 h followed by aging treatment.